PENGEMBANGAN PENUNTUN PRAKTIKUM MENGGUNAKAN APLIKASI FLIP PDF TERHADAP KETERAMPILAN PRAKTEK RESUSITASI NEONATUS PADA MAHASISWA - Silvanora, Rice; Osvinarti, Osvinarti (NHM PRESS, 2024)
The development of teaching materials is an effort to support the learning process by optimally utilizing the functions of development and management. The practice of resuscitation is a series of learning processes from the course on neonatal, infant, toddler, and preschool child care. This course is included as a core subject in the Midwifery Department. Therefore, participants in the practice need to have practical skills through easily understandable media, one of which is the flip PDF file. By using a flip PDF file, one can obtain information without wasting much time and can carry it anywhere to achieve effective, efficient, and engaging learning. Using research and development methods (Research and Development). Then an experiment was conducted in the form of a one group pre-test and post-test design. Statistical analysis test using the Paired Sample T test and the Wilcoxon Signed Ranks Test. The results of this study indicate that the practical guide using Flip PDF is deemed feasible and valid for use, with validation from subject matter experts at 97.5%, categorized as very valid, learning experts at 100%, also categorized as very valid, and media experts at 97.9%. Based on the calculation of student response questionnaire data regarding the developed Flip PDF practical guide, the percentages for each assessed aspect are as follows: 93.6% for the technical aspect, 92.8% for the construction aspect, and the didactic aspect has a percentage of 96.1%. Overall, the average percentage of these three aspects is 94.2%, with criteria classified as very good. The results of the data analysis showed a p value = 0.00 or p < 0.05, indicating that there is an effect of using practical guide tools through the Flip PDF application on the neonatal resuscitation skills of fourth-semester students in the applied midwifery program in 2024.